Molecular Mechanisms and Signaling Pathways Involved in Sertoli Cell Proliferation - Meroni, Silvina Beatriz; Galardo, María Noel; Rindone, Gustavo; Gorga, Agostina; Riera, María Fernanda; Cigorraga, Selva Beatriz (Frontiers in Endocrinology, 2019)
Sertoli cells are somatic cells present in seminiferous tubules which have essential roles in regulating spermatogenesis. Considering that each Sertoli cell is able to support a limited number of germ cells, the final number of Sertoli cells reached during the proliferative periods determines sperm production capacity. Only immature Sertoli cells, which have not established the blood-testis barrier, proliferate. A number of hormonal cues regulate Sertoli cell proliferation. Among them, FSH, insulin family of growth factors, activin and cytokines action must be highlighted. It has been demonstrated that cAMP/PKA, ERK1/2, PI3K/Akt and mTORC1/p70SK6 pathways are the main signal transduction pathways involved in Sertoli cell proliferation. Additionally, c-Myc and hypoxia inducible factor are transcription factors which participate in the induction by FSH of various genes of relevance in cell cycle progression. Cessation of proliferation is a pre-requisite to Sertoli cell maturation accompanied by the establishment of the blood-testis barrier. To this respect, the participation of androgens, estrogens, thyroid hormones, retinoic acid and opioids has been reported. Additionally, two central enzymes that are involved in sensing cell energy status have been associated with the suppression of Sertoli cell proliferation, namely AMPK and Sirtuin 1 (SIRT1). Among the molecular mechanisms involved in the detention of proliferation and in the maturation of Sertoli cells, it is worth mentioning the up-regulation of the cell cycle inhibitors p21Cip1, p27Kip and p19INK4, and of the gap junction protein connexin 43. A decrease in Sertoli cell proliferation due to the administration of certain therapeutic drugs and to the exposure to xenobiotics agents before puberty has been experimentally demonstrated. This review focuses on the hormones, locally produced factors, signal transduction pathways and molecular mechanisms controlling Sertoli cell proliferation and maturation. The comprehension of how the final number of Sertoli cells in adulthood is established constitutes a prerequisite to understand the underlying causes responsible for the progressive decrease in sperm production that has been observed during the last 50 years in humans.